Ballad as a genre of medieval English poetry - Ahmedova Marhabo , Ibragimova Dilafruz (Journal of Innovation in Education and Social Research, 2024)
Popular ballads were anonymous narrative poems, written in short stanzas of two or four lines, rhyming abcb. There is a mixture of dialog and narration, the speaker does not introduce his personality and there is no moralizing or didactic approach. This article describes ballad as a genre of medieval English poetry.